Introducing Machine Learning Through a Multisensory Approach for Young People with Down Syndrome - Aquini, Lui Gill; Veiga, Júlia; Primo, Tiago Thompsen; Foss, Luciana; Cavalheiro, Simone André da Costa; Rosa Junior, Leomar Soares da; Jurgina, Laura Quevedo (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2025: Anais do XXXVI Simpósio Brasileiro de Informática na Educação, 2025)
This paper presents an ongoing educational activity to introduce Machine Learning concepts to children and young people with Down Syndrome. In Brazil, the lack of a standard for Computer Science Education until 2022 led to disparities, with public schools often lacking resources. A 2022 regulation made Computing mandatory in K-12, aligning with the Brazilian National Common Curricular Base, which includes Artificial Intelligence-related competencies. In the Brazilian context, Computing is still not part of the school curriculum for most students without disabilities. Students with developmental disorders, such as Down Syndrome, have even less access to activities designed to teach computational skills in their learning environments. However, it is possible to observe that, when provided with technologies adapted to their needs, these students can learn and develop effectively. Therefore, this work proposes a multisensory unplugged activity tailored to introduce Machine Learning concepts to people with Down Syndrome. Given the multisensory approach, we expect to observe benefits beyond computational learning, promoting the development of fine motor skills through a playful and fun experience.